DISCOVERING AND RESEARCH OF SA HUYNH CULTURE (1909 - 2019) - Lâm Thị Mỹ Dung (Tạp chí Khoa học Đại học Đà Lạt)
In 1909, a short report by Vinet (1909) announced the "Discovery of a depot containing about 200 earthen mortuary containers which was buried not deep in the sand dune in the coastal area of Sa Huynh". This was the first announcement, opening a series of excavations and archaeological research in later years in Ducpho district (Quangngai). In 1923, Labarre went to Sa Huynh to carry out the excavation, and the excavation results were reported in Parmentier's work "The depot of Sa Huynh jar burials in Quangngai, An Nam" in the journal of the EFEO (volume 24) published in Hanoi. The artifacts obtained from this excavation have been kept at the Museum of Vietnamese History to the present day. After this excavation, many other studies were published, and it is worthy of note that in 1936 the term Sa Huynh culture was proposed by Colani (1936). After 1975, along with the sites belonging to Sa Huynh culture in Quangngai, Vietnamese and foreign archaeologists have recognized and studied many Pre Sa Huynh, Sa Huynh, and Sa Huynh-like cultural sites in various localities in the Central Highlands and Southern Vietnam. The article describes the outstanding achievements of the archaeologists regarding the Sa Huynh culture since its discovery. New insights and knowledge about the nature, characteristics, chronology, origins, owners and cultural relations are also further commented on in this study. Some issues that need further research to conserve andpromote the value of the heritage are also mentioned.